"I didn't support PrEP because I didn't know what it was": Inadequate information undermines male partner support for young women's pre-exposure prophylaxis use in western Kenya. Issue 3 (3rd July 2022) - Agot, Kawango; Hartmann, Miriam; Otticha, Sophie; Minnis, Alexandra; Onyango, Jacob; Ochillo, Marylyn; Roberts, Sarah T
Abstract : The HIV infection rate is higher among adolescent girls and young women (AGYW) in Africa than men in the same age range. Pre-exposure prophylaxis (PrEP) can be used by women discreetly; however, for most AGYW, male partner approval is desired. We explored PrEP use in the context of relationship violence and power dynamics through focus group discussions and support club sessions with AGYW, in-depth interviews and male sensitisation sessions with male partners of AGYW, and joint sessions with AGYW and their male partners. Many male partners reported hesitancy in supporting partner's PrEP use without sufficient information; most of these became supportive following their engagement in study activities; and most preferred participation in decisions around PrEP use. For AGYW, male involvement minimised partner violence around their PrEP use. The findings support the need for correct PrEP information to be provided to male partners of AGYW and to involve them early on, in decision-making about PrEP use. This is likely to improve uptake of and adherence to PrEP.